Health care utilisation changes among Alaska Native adults after participation in an indigenous community programme to address adverse life experiences: a propensity score-matched analysis. Issue 1 (1st January 2020) - Ray, Lily; Outten, Bobbi; Gottlieb, Katherine
ABSTRACT: The aim of this study was to investigate whether participation in Family Wellness Warriors Initiative (FWWI), an Alaska Native program that addresses adverse life experiences, is associated with changes in health care utilisation. The study method was a propensity score-matched cohort analysis using retrospective electronic health record data from Southcentral Foundation, a tribal health care system, from 2012 to 2017. Ninety p\articipants in FWWI trainings were identified as the intervention cohort and were propensity matched with 90 people who participated in other emotional wellness-related interventions. The primary outcome was the number of total health system visits. Secondary outcomes included emergency department (ED) visits, substance-use visits and visits with somatisation potential. After adjustment for covariates, FWWI participants showed a 36% reduction in total system visits (incidence rate ratio 0.64, 95% CI 0.49–0.84) and a 70% reduction in substance use visits (incidence rate ratio 0.30, 95% CI 0.10–0.93) when compared to the control. FWWI participants showed a 40% reduction in ED visits (incidence rate ratio 0.60, 95%CI 0.35–1.02) when compared to the control that was borderline significant. No significant differences were found for visits with somatisation potential (incidence rate ratio 1.25, 95% CI 0.79–1.99).